A Comparative Thematic Analysis of the Poems I Told Him by Ada Jafri and We Sinful Women by Kishwar Naheed - Anwar, Nazia; Malik, Moazzam Ali; Butt, Isha Razzaq (Pakistan Languages and Humanities Review, 2024)
The main aim of the current research is to highlight the main themes and stylistic differences in both the stories, I Told Him and We Sinful Women to analyze how the two authors manifest female identity, silence and revolt. Feminist poetry has become a strong voice of women and their struggle against patriarchy as expressed through Pakistani feminism poetry. Ada Jafri and Kishwar Naheed are the two most prominent Urdu poets who have transformed the notion of womanhood by relying on clear but overlapping poetic voices. The study applies a qualitative comparative thematic analysis approach in a feminist-postcolonial context by utilizing diction, imagery, tone, and symbolism to find latent ideological meanings. Findings of the study unearth that the poem of Jafri is full of suppressed self-exploration, whereas, that of Naheed’s is an expression of group resistance. They both confront gender subjugation yet in two different expressive modes subtle resistance and overt rebellion. The research concludes that the Urdu feminist poetry is being developed as an expression of personal emotional claim into the collective empowerment, which is representative of the larger shift in the voice of women in Pakistani literature. The study recommend that the feminist Urdu poetry should be included in schools’ curricula as a way of fostering gender sensitization as well as appreciation of culture